﻿Into the unknown: the first barcode-assisted checklist of Psocoptera (Insecta, Psocodea) of Georgia with a census on country species richness - Armen Seropian; Eka Arsenashvili; Natalia Bulbulashvili; Anano Shubashishvili; Giorgi Iankoshvili; Mariami Todua; Ana Ananiashvili; Shota Japarashvili; Tinatin Chkhartisvhili; Aleksi Memishishi; Sopio Balkhamishvili; Beka Chitadze; et al. (ZooKeys, 2023)
This checklist reports 47 species of Psocoptera from 15 families and three suborders from Georgia, of which 31 species are recorded for the first time, increasing the known fauna of the country by more than 65%. Of these, 37 species have been barcoded, representing 210 Barcode Identification Numbers (BINs). An additional 14 species are expected to occur in Georgia but remain undiscovered, meaning that only ≈ 77% of the fauna is currently documented. Barcodes, comments on distributions, and images of voucher specimens are given followed by a map of the sampling sites.